2018
DOI: 10.1155/2018/2149564
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Tunnel Endoscopic Resection for Esophageal Submucosal Tumors: A Multicenter Study

Abstract: Background Submucosal tumors (SMTs) are primarily benign tumors, but some may have a malignant potential. Endoscopic submucosal dissection that has been used for removing esophageal SMTs could cause perforation. Submucosal tunnel endoscopic resection (STER) is an improved and an effective technique for treating esophageal SMTs. Aims This study was conducted to evaluate the efficacy and safety of STER for treating esophageal SMTs. Methods A retrospective study design was adopted to analyze the baseline characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…[ 19 , 20 ] Furthermore, several studies revealed that endoscopy could achieve en bloc resection in case of esophageal GISTs, and endoscopic resection is safe, effective, and minimally invasive. [ 2 , 8 , 21 , 22 ] Moreover, several lymphomas presented as SELs and treated with endoscopic resection have been reported. [ 23 27 ] In addition, according to the literature review, some other rare cases were treated with endoscopy, similar to follicular dendritic cell sarcoma and adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 19 , 20 ] Furthermore, several studies revealed that endoscopy could achieve en bloc resection in case of esophageal GISTs, and endoscopic resection is safe, effective, and minimally invasive. [ 2 , 8 , 21 , 22 ] Moreover, several lymphomas presented as SELs and treated with endoscopic resection have been reported. [ 23 27 ] In addition, according to the literature review, some other rare cases were treated with endoscopy, similar to follicular dendritic cell sarcoma and adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal subepithelial lesion (SEL) is rare, accounting for <1% of all esophageal tumors. [ 1 , 2 ] SELs originate from the muscularis mucosa, submucosa, or muscularis propria and are often covered with normal epithelium. [ 3 ] They usually do not produce obvious clinical symptoms and are thus often incidentally found.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that STER is a safe and effective treatment for the resection of esophageal SMTs; however, we found over the course of the study that for some special esophageal SMTs, such as those located in the upper esophagus or cardia or those > 3.5 cm in size, due to the limited space in the tunnel and the operative difficulty, the operation time would be longer and the complication rates of STER would greatly increase. In 2015, Jun et al [21] first reported successful opening of the mucosa on the distal end of the tunnel during STER to resect a 40-mm esophageal SMT. In 2017, Zhang et al [22] reported 10 cases of SMTs near the cardia that were successfully resected using submucosal tunneling endoscopic resection with double opening (DO-STER), which demonstrated that DO-STER is safe and effective for removing SMTs located within the cardia.…”
Section: Discussionmentioning
confidence: 99%